Culturally Responsive Teaching: A Systematic Review of Educational Practices and Implications - Alamsyah, Trian Pamungkas; Fathurrohman, Maman; Rosmilawati, Ila (Universitas Pendidikan Ganesha, 2025)
The concept of multiculturalism has been widely discussed, but its implementation in various educational environments shows less variation. This study aims to analyze various studies related to CRT to identify patterns, supporting factors, and their impact on learning. This type of research uses the systematic literature review (SLR) methodology. The sample in this study consists of scientific articles that discuss the practice and implications of culturally responsive teaching in formal educational contexts, both at elementary, secondary, and higher levels. The data collection method in this study was carried out through a systematic literature search process using academic databases. The data analysis method used in this study is thematic analysis, which aims to identify, group, and interpret the main patterns that emerge from the articles reviewed. The results of the study indicate that CRT is able to improve learning outcomes, student engagement, and the development of critical thinking skills. This approach is also practical in bridging the cultural gap between students and learning materials, creating an inclusive environment, and supporting the development of soft skills such as collaboration and problem-solving. The implications of this study are to show that culturally responsive teaching can increase student engagement, strengthen cultural identity, and encourage a more inclusive learning environment. Therefore, educational institutions and policymakers need to consider integrating this approach into the curriculum, learning planning, and teacher training and professional development programs.